2003
DOI: 10.1038/sj.cdd.4401307
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial fusion of human trophoblast depends on caspase 8

Abstract: Differentiation of human placental villous trophoblast includes syncytial fusion of cytotrophoblast forming syncytiotrophoblast. Early stages of the apoptosis cascade were described to be involved in this differentiation process. We investigated the role of the initiator caspase 8 in syncytial fusion in vitro, cultivating placental villous explants with or without caspase 8 antisense oligonucleotides or peptide inhibitors for up to 120 h. Trophoblast fusion and differentiation were assessed by confocal microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 56 publications
1
84
0
1
Order By: Relevance
“…Inhibition of the caspase 8 expression in human placental explants inhibits the progression of the apoptosis cascade and, thus, syncytial fusion. 30 Therefore, a controlled rate of apoptosis in the trophoblast layer is essential; imbalance in trophoblast turnover may lead to insufficient villi formation or degeneration of SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the caspase 8 expression in human placental explants inhibits the progression of the apoptosis cascade and, thus, syncytial fusion. 30 Therefore, a controlled rate of apoptosis in the trophoblast layer is essential; imbalance in trophoblast turnover may lead to insufficient villi formation or degeneration of SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorothioate oligonucleotides and controls were designed and manufactured by Biognostik (Gottingen, Germany) (sequence in Table 2). Floating villous and extravillous explants were incubated in the presence of either 1 mM antisense oligonucleotides, sense oligonucleotides control, 100 nM siRNA or non-silencing siRNA control (n ¼ 9) (as described in Black et al 30 ). Nontreated controls showed no significant difference compared with the non-silencing control (data not shown).…”
Section: First Trimester Villous Explant Culturesmentioning
confidence: 99%
“…72 Using antisense oligonucleotides and caspase inhibitors, it was shown that activation of caspase-8 is essential during differentiation of human placental villous trophoblasts. 74 Another report established a role for caspase-3 in skeletal muscle differentiation: primary myoblasts from caspase-3 knockout mice displayed a severe lack of myotube and myofiber formation and a reduced expression of musclespecific genes. 75 Furthermore, the authors identified the serine/threonine Mammalian Sterile Twenty-like kinase (MST1) as a crucial effector of caspase-3, since a proteolytic fragment of MST1 rescued the differentiation defect of caspase-3 deficient myoblasts.…”
Section: Caspases In Cell Differentiationmentioning
confidence: 99%
“…Not determined Caspase- 8 Proliferation of T, B and NK cells 14,39,40 NF-kB activation following TcR-, TNF-, TLR-4-and Apo2/TRAIL-stimulation 5,12,16 dsRNA-induced NF-kB activation via its prodomain 25,26 Differentiation of monocytes into macrophages 72,73 Differentiation of placental villous trophoblasts 74 Caspase-9 Not determined Caspase-10 dsRNA-induced NF-kB activation via its prodomain 25,26 Caspase-11 Maturation of pro-inflammatory cytokines 102 Caspase-12 Attenuation of inflammation and susceptibility to sepsis 94,95 Caspase-14 Terminal differentiation of keratinocytes? 70,103 11 With the notable exception of DREDD, RNAi-mediated knockdown of the other fly caspases did not affect Relish processing in cells.…”
mentioning
confidence: 99%
“…26 Notably, caspase-8 has also been implicated in the differentiation of the human placental trophoblast, by mediating the syncytial fusion of the cytotrophoblast that accounts for the generation of the syncytiotrophoblast. 27 Loss-of-function mutations in the human caspase-8 gene cause defects in the activation of T, B and NK cells, culminating in immunodeficiency. 28 Similarly, knockout of caspase-8 (or that of its cytosolic adaptor FADD, i.e.…”
Section: Vital Functions Of Mammalian Caspasesmentioning
confidence: 99%